God's Marshall plan American Protestants and the struggle for the soul of Europe - Strasburg, James D. ca. 20./21. Jh. (New York, NY Oxford University Press, 2021)
"God's Marshall Plan explores the origins of Christian nationalism and Christian globalism-two competing theologies of global engagement-in the twentieth-century American Protestant encounter with Europe. It recovers the story of the American Protestants who crossed the Atlantic in an era of world war, tracked the rise of totalitarian dictators, mobilized against the Axis powers, and identified Europe as a continent in need of saving. In response, they launched far-reaching missions to spread their faith and democracy across the Atlantic. As they joined army platoons in occupying Germany, they singled out the defeated nation as the prime European territory for a new American-led, Christian and democratic world order that could thwart any totalitarian threat. Throughout these efforts, however, American Protestants realized they had come to dramatically different conclusions about how to rebuild Europe out of the ruins of war. Their diverging visions ultimately sparked a spiritual struggle for the continent and leadership of the postwar world. All the while, European Protestants began to sharply protest America's spiritual advance. Faced by this challenge, a growing number of ecumenical Protestants rethought their efforts to build God's kingdom through America's global strength. Forsaking their wartime nationalism, they championed a new theology of global fellowship, reconciliation, and justice. A fresh wave of Protestant cold warriors surged forward, however, to retake their nation and promote a theology of spiritual liberty and anti-communism across the Atlantic. The spiritual struggle for Europe thus left American Protestants deeply divided and at odds over their global mission. It ultimately forged competing visions of global engagement that transformed the United States, diplomacy, and politics in the Cold War and beyond"--
Includes index
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Nationalism -- Religious aspects -- Christianity; Protestants -- Political activity -- Europe; Protestants -- Political activity -- United States; Religion And Politics -- Europe -- History; Religion And Politics -- United States -- History; Protestantism -- Europe -- History -- 20th century; Protestantism -- United States -- History -- 20th century; Nationalism -- Religious aspects -- Christianity; Europe -- Relations -- United States; United States -- Relations -- Europe